Insights into the Enhancement Mechanisms of Molten Salt Nanofluids - Xiong Yaxuan; Wang Huixiang; Wang Zhenyu; Wu Yuting; Xu Qian; Wang Gang; Li Chuan; Ding Yulong; Ma Chongfang (International Journal of Photoenergy)
The addition of nanomaterials to molten salts can significantly improve their thermal performance. To explore the enhancement mechanisms, this work prepared carbonate salt nanofluids with binary carbonate as base salt and 20 nm SiO2 and 20 nm MgO nanoparticles as additives by the commonly used aqueous solution method. Then, the key performance and micromorphology of the carbonate salt nanofluids are characterized by differential scanning calorimetry, thermal gravimetric analysis, laser flash analysis, and micromorphology analysis. Results showed that the 20 nm SiO2 nanomaterials instead of the 20 nm MgO nanomaterials exerted higher effects on latent heat while the 20 nm MgO nanomaterials instead of the 20 nm SiO2 nanomaterials exerted higher effects on the sensible heat, thermal conductivity, and high-temperature stability of carbonated salt. In addition, different nanostructures were observed in SiO2-based and MgO-based molten salt nanofluids, respectively. Innovatively, formation mechanisms of molten salt nanofluids were proposed based on cloud nuclei to explain the different enhancements in this work.